2014
DOI: 10.5539/elt.v7n5p120
|View full text |Cite
|
Sign up to set email alerts
|

One Stone, Two Birds: Maximizing Service Learning Outcomes through TESOL Practicum

Abstract: This paper examines a good practice for service learning that has been implemented for years in TESOL Internship, a professional unit for students doing Master of Arts (MA) in Teaching English to Speakers of Other Languages (TESOL) at a major university in Australia. The author has investigated and identified three key features of a good practice in service learning, including critical reflection, community engagement and intercultural communication, which are evidenced in student service learning in various E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
1
1
0
1
Order By: Relevance
“…Regarding changes in professional knowledge, the findings of this study indicated that ASL practical experiences contributed to participants' confident application of TEFL teaching theories. This coincides with numerous studies suggesting that SL amplifies academic knowledge when applied in practical teaching environments (Cho and Gulley 2017;Simsek 2020;Yang 2014). However, Goodwin et al (2014) noted some discrepancies in their findings and that some participants felt overwhelmed when applying theoretical knowledge in real classroom situations.…”
Section: Acquiring Insights Into Child Learning Behaviourssupporting
confidence: 86%
“…Regarding changes in professional knowledge, the findings of this study indicated that ASL practical experiences contributed to participants' confident application of TEFL teaching theories. This coincides with numerous studies suggesting that SL amplifies academic knowledge when applied in practical teaching environments (Cho and Gulley 2017;Simsek 2020;Yang 2014). However, Goodwin et al (2014) noted some discrepancies in their findings and that some participants felt overwhelmed when applying theoretical knowledge in real classroom situations.…”
Section: Acquiring Insights Into Child Learning Behaviourssupporting
confidence: 86%
“…Outra área, certamente não menos importante, é constituída pela remoção das barreiras linguísticas que dificultam o fluxo de informação e o encontro das diversidades culturais. Ademais, o ensino e a formação de professores de línguas estrangeiras são duas áreas às quais o service-learning tem sido aplicado com sucesso (Ping, 2014;Salgado-Robles, 2018). Na área da tradução, assim como no service-learning, existe uma forte participação voluntária de tradutores profissionais e em formação, que oferecem seu trabalho gratuita-mente em associações como Translators without Borders, Traduttori per la Pace ou Translation Commons.…”
Section: Service-learning Tradutório E Formação Do Tradutorunclassified
“…The findings of this study confirmed that implementation of team teaching in initial teacher education has the potentiality of enhancing the learning experience of pre-service teachers, with more structured forms of feedback and support developing from mentors and peers as a result of the approach. This study also suggested that team teaching can potentially generate more collaborative activities in class activities as student teachers are encouraged to implement more group collaborative activities and increase student talking time (Yang, 2014).…”
Section: Team Teaching In Initial Foreign/second Language Teacher Edumentioning
confidence: 99%